Financial distress for bankruptcy early warning by the risk analysis on go-public banks in Indonesia - Laely Aghe Africa (Universitas Hayam Wuruk Perbanas, 2016)
Early warning is essential for overseeing the firm’s financial system stability, and is developed by financial distress model. Financial Distress is financial declining phase that happens before bankruptcy or liquidation. This Research aimed to analyze whether the following factors such as CKPN (Allowance For Impairment Losses Of Credits), NPL (Non Performing Loan), IRR (Interest rate Ratio), PDN (Net Open Position), LDR (Loan To Deposit Ratio), IPR (Investing Policy Ratio), OE-OI (Operating Expenses To Operating Revenues) and FBIR (Fee Based Income Ratio) can determine financial distress as early warning in Indonesia’s go public banks. It is a quantitative study, with the sample of 100 go-public banks listed in Indonesia Stock Ex-change (www.idx.go.id) ranging from 2010 to 2014, collected using purposive sampling. They were analyzed using SPSS 23 IBM version. The result shows that LDR (Loan To Deposit Ratio) is the most significant factor to determine financial distress as early warning of bankruptcy of Indonesia’s go public banks. Besides that, it has several implications for regulators and bank management to determine the firm financial system stabilization.